Prática pedagógica inovadora nas aulas de Educação Física: uma construção a partir do tênis de campo - Silva Junior, Francisco Lindosmar da (2025)
The proposal for this study arose from concerns about pedagogical practices and their development during lessons, identifying three categories: traditional (sports-oriented), abandonment of teaching work ("just let them play"), and innovative practices. The term "innovative pedagogical practices" (IPP) stood out, and with the interest of better understanding this teaching approach, the objective of this study was to explore innovative pedagogical practices in Physical Education classes using tennis as a starting point. This qualitative research was conducted with 6th-grade students in a public school within a municipal education network in the interior of São Paulo, covering 19 tennis lessons. Data collection was carried out through lesson journals produced by the researcher, who was also the Physical Education teacher of the class.The analyzed data led to the identification of the following categories: a) Pre-game, in which the following codes were identified: content, methodology, theory vs. practice relationship, assessment, and schedule. These are concepts explored by the teacher even before engaging with students, incorporated into lesson planning, and revisited whenever adjustments are necessary. When well-planned, these concepts can support the development of an IPP. b) Our game, in which the following codes were identified: internal logic, external logic, adaptations, and student protagonism. These bring in concepts that can directly influence the development of activities when explored within the perspectives of IPP, facilitating content understanding, enhancing participation, and increasing student engagement. Throughout the research, it was possible to identify that actions surrounding IPP consist of multiple elements that require careful planning and teacher involvement, as well as reflection on ingrained teaching practices. It is necessary to break away from teaching models where the student is merely a passive recipient of knowledge and instead position them as protagonists in the teaching and learning process, while also exploring the various forms of knowledge derived from movement culture.